Method for improving photoelectric conversion efficiency of perovskite solar cell

By using materials with Cl-C=N structure to work synergistically with amide molecules to generate Cl-containing intermediate products and participate in the crystallization process of perovskites, the problem of rapid decline in performance and stability of perovskite solar cells after large-area is solved, and a high-efficiency and high-stability perovskite solar cells are achieved.

CN119816180APending Publication Date: 2025-04-11HUBEI WONDER SOLAR LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510031669.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The performance and stability of perovskite solar cells have rapidly declined after large-scale areas, resulting in a significant reduction in photoelectric conversion efficiency, limiting their commercial promotion.

Method used

Materials with Cl-C=N structure work together with amide molecules to generate Cl-containing intermediate products, participate in the crystallization process of perovskites, and improve the crystallinity and uniformity of perovskite films.

Benefits of technology

By improving the crystallization quality of perovskite films, reducing defects in the crystals, significantly improving the photoelectric conversion efficiency and stability of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816180A_ABST
    Figure CN119816180A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving photoelectric conversion efficiency of a perovskite solar cell. The photoelectric conversion efficiency of the perovskite solar cell can be improved through the reaction of the additive and the amide solvent molecules in the perovskite precursor solution. The additive has a structure as shown in a formula (I); in the formula, R1, R2 and R3 are respectively and independently selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino and substituted or unsubstituted guanidino; x <-> is selected from halogen anions, SCN <->, CN <->, OCN <->, OH <->, COO <->, CH3SO3 <-> or CF3SO3 <->.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, and in particular to a method for improving the photoelectric conversion efficiency of perovskite solar cells. Background Art

[0002] With the rapid development of social economy, global energy consumption continues to rise. However, the reserves of fossil fuels are limited, and they will cause serious pollution to the environment during development and use. It is difficult to meet the growing energy demand and the goal of sustainable development. Therefore, the development of alternative energy is particularly important. As an abundant renewable resource, solar energy can be converted into various types of energy to meet global needs, showing great development potential. Among the existing solar energy utilization technologies, photovoltaic power generation technology (PV) based on solar cells has broad development prospects by directly converting solar energy into electrical energy. In recent years, new solar cells represented by inorganic-organic-inorganic lead halide perovskite solar cells (PSCs) have attracted extensive attention from researchers at home and abroad in the photovoltaic field due to their low cost and high conversion efficiency.

[0003] However, the problem that restricts the commercialization and promotion of perovskite solar cells is the rapid decline in performance and stability after the large-scale application of the battery device, which seriously affects its future development. 2 ) has a photoelectric conversion efficiency of more than 26%, but when the perovskite solar cell device area is enlarged (area larger than 10cm 2 ), its photoelectric conversion efficiency will drop significantly (to about 10%), which is mainly due to the deterioration of perovskite crystallinity and uniformity after the device area is enlarged; at the same time, the device stability will also decrease, further restricting the commercialization process of perovskite solar cells. In order to obtain large-area perovskite solar cell modules with both high efficiency and high stability, improving the crystallization quality is the key to obtain large-area perovskite solar cell modules with high efficiency and high stability.

[0004] In perovskite solar cell devices, charge separation efficiency, charge transport and diffusion length of carriers are all affected by the crystallinity of perovskite. Therefore, the formation of dense, pinhole-free large-grain, high-crystallinity perovskite crystals is the key to preparing high-performance perovskite solar cells. In the past decade, a variety of methods have been developed, such as anti-solvent method, two-step method, vacuum flash evaporation, post-treatment and other process methods, solvent engineering, additive engineering and other chemical means to solve the crystallinity of perovskite crystals and realize efficient and stable perovskite solar cells and components. For example, DMSO mainly generates PbI2(DMSO)x intermediate phase through the strong coordination of DMSO and Pb, thereby delaying the crystallization process of perovskite crystals and realizing the preparation of uniform and high-quality perovskite films. This solution has been highly recognized in the field. In addition, adding Cl-containing additives such as MACl to the precursor is also widely used to regulate the crystallization process of perovskite films, thereby obtaining high-quality perovskite films, greatly improving the absorption of light by perovskites and the charge transfer performance of the films, and significantly improving the photoelectric conversion efficiency of the device. This scheme has now become a widely used scheme in the industry. Almost all high-efficiency devices have MACl involved in the deposition process of perovskite films (Nature volume 616, pages 724–730 (2023)). At present, commonly used chloride-containing additives, such as chloromethylamine (MACl) or formamidine chloride (FACl), have a boiling point of more than 120°C and are usually difficult to completely remove. Although residual Cl has been reported to have a passivation effect and improve the efficiency of the device, subsequent studies have shown that residual Cl will reduce the long-term working stability of the device, which is not conducive to the industrialization process of perovskite solar cells.

[0005] How to improve the photoelectric conversion efficiency of perovskite solar cells still needs to be improved. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. The present invention provides a method for improving the crystallinity and uniformity of perovskite films (especially large-area perovskite films) by utilizing the synergistic effect of materials with a Cl-C=N structure and amide molecules (such as N-methylformamide, N,N-dimethylformamide, etc.), thereby improving the photoelectric conversion efficiency of perovskite solar cells. The highly active part with a Cl-C=N structure can react with the amide material to generate a Cl-containing intermediate product and participate in the crystallization process of the perovskite, inducing the perovskite crystal to achieve uniform and dense high-quality crystallization, reducing defects in the perovskite crystal, and improving the photoelectric conversion efficiency and stability of the perovskite solar cell. The synergistic use of the two materials provides a new idea for the development of perovskite solar cell modules.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] The first aspect of the present invention provides an additive for a perovskite solar cell having a structure shown in formula (I);

[0009]

[0010] Wherein, R1, R2, and R3 are each independently selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino, and substituted or unsubstituted guanidino;

[0011] X - Selected from halogen anions, SCN - , CN - 、OCN - OH - 、COO - 、CH3SO3 - , or CF3SO3 - .

[0012] The additive used in the preparation of perovskite solar cells has significantly improved the overall performance of perovskite solar cells, especially the photoelectric conversion efficiency of perovskite solar cells. The introduction of this additive not only provides new ideas for the engineering application of perovskite materials, but also lays a solid foundation for the future development of efficient and low-cost photovoltaic technology.

[0013] Preferably, R1, R2, and R3 are each independently selected from H, substituted or unsubstituted C 1~4 alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino, substituted or unsubstituted guanidino, the C 1-4 The alkyl group, amino group, amidino group and guanidino group may be independently substituted by one or more alkyl groups, aryl groups, halogenated alkyl groups, halogenated aryl groups and amino groups.

[0014] Preferably, R1 and R2 are H, and R3 is H, CH2, CH2CH3, or CH2CH2CH2CH3.

[0015] The X - F - , Cl - OH - .

[0016] Preferably, at least one of the following is selected:

[0017]

[0018] A second aspect of the present invention provides a precursor solution for a perovskite solar cell, comprising a perovskite material, the additive for a perovskite solar cell according to the first aspect, and an amide material.

[0019] The additive provided by the present invention is used for perovskite solar cells. The additive first reacts with amide molecules to form a Cl-containing intermediate product. The intermediate product plays a key role in the subsequent perovskite crystallization process. During the perovskite crystallization process, the nucleation and growth of the perovskite crystal can be effectively regulated, the crystallization quality of the perovskite crystal is improved, and thus the photoelectric conversion efficiency of the perovskite solar cell is improved.

[0020] According to an embodiment of the present invention, the molar ratio of the additive for perovskite solar cells to the amide material is 0.1:(2-100).

[0021] According to an embodiment of the present invention, the amide material has a structure shown in formula (II):

[0022]

[0023] Wherein R4, R5, and R6 are each independently selected from substituted phenyl or unsubstituted phenyl, H, CH3, CH2CH3, CH2CH2CH3, NH2, CH2NH2, CH2CH2NH2, or NHNH2.

[0024] Preferably, R4, R5, and R6 are each independently selected from H, CH2CH3, CH3, or NH2.

[0025] Preferably, the substituted phenyl mentioned refers to a phenyl group substituted by one or more alkyl groups, aryl groups, haloalkyl groups, or haloaryl groups.

[0026] A third aspect of the present invention provides a perovskite solar cell, comprising a perovskite active layer, wherein the perovskite active layer comprises a perovskite material, the additive for a perovskite solar cell according to the first aspect, and an amide material;

[0027] According to an embodiment of the present invention, the molar ratio of the additive for perovskite solar cells to the perovskite material is (0.005-0.2): 1. According to a preferred embodiment, the molar ratio of the additive for perovskite solar cells to the perovskite material is (0.1-0.2): 1.

[0028] A fourth aspect of the present invention provides a perovskite solar cell, comprising:

[0029] Conductive substrate;

[0030] A dense layer, the dense layer is disposed on the conductive substrate;

[0031] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is disposed on the dense layer;

[0032] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;

[0033] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;

[0034] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the product of the reaction between the additive for perovskite solar cells described in the first aspect and the amide material is added to the perovskite precursor solution for preparing the perovskite active layer.

[0035] According to an embodiment of the present invention, the conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;

[0036] The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;

[0037] The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;

[0038] The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3;

[0039] The material of the porous counter electrode layer is carbon.

[0040] According to an embodiment of the present invention, the perovskite solar cell includes: the additive for the perovskite solar cell and the amide material are added to the perovskite precursor solution and are jointly filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.

[0041] The beneficial effects achieved by the present invention are at least:

[0042] The present invention provides a method for improving the crystallinity and uniformity of a large-area perovskite film by using the synergistic effect of a material having a Cl-C=N structure and amide molecules (such as N-methylformamide, N,N-dimethylformamide, etc.), thereby improving the photoelectric conversion efficiency of a perovskite solar cell. The Cl-C=N high-activity part of the molecule can react with the amide to generate a Cl-containing intermediate product and participate in the crystallization process of the perovskite, inducing the perovskite crystal to achieve uniform and dense high-quality crystallization, reducing defects in the perovskite crystal, and improving the photoelectric conversion efficiency and stability of the perovskite solar cell. The additive material having a Cl-C=N structure and the amide material synergistically act to prepare the perovskite active layer of the perovskite solar cell, and then to prepare the perovskite solar cell, thereby providing a new idea for the development of perovskite solar cell modules. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a physical picture of the control group perovskite solar cell provided according to Example 1 of the present invention.

[0044] Figure 2 This is a physical picture of the experimental group of perovskite solar cells provided according to Example 1 of the present invention. DETAILED DESCRIPTION

[0045] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0046] The present invention provides a material with a Cl-C=N structure, which can be used as an additive for a perovskite solar cell and can be used to improve the photoelectric conversion efficiency of the perovskite solar cell by synergistically acting with an amide material.

[0047] The additive has a structure shown in formula (I);

[0048]

[0049] Wherein, R1, R2, and R3 are each independently selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino, and substituted or unsubstituted guanidino;

[0050] X - Selected from halogen anions (such as F - , Cl - Br - etc.), SCN - , CN - 、OCN - OH - 、COO- 、CH3SO3 - , or CF3SO3 - .

[0051] According to a specific embodiment, the amidine group mentioned can be acetamidine, propionamidine, butyramidine, pentamidine, etc.

[0052] The substituents mentioned are not limited to alkyl (according to a preferred embodiment, C 1-4 The substituents mentioned above can be used to adjust the electron cloud density on N and S=O.

[0053] The above additives can work synergistically with amide materials to improve the crystallinity and uniformity of large-area perovskite films, thereby improving the photoelectric conversion efficiency of perovskite solar cells.

[0054] According to a specific embodiment, the amide material mentioned has a structure shown in the following formula (II):

[0055]

[0056] R4, R5, R6 are each independently selected from substituted phenyl or unsubstituted phenyl (according to a preferred embodiment, the phenyl is replaced by one or more alkyl groups such as C 1-4 alkyl, aryl, haloalkyl, haloaryl), H, CH3, CH2CH3, CH2CH2CH3, NH2, CH2NH2, CH2CH2NH2, or NHNH2.

[0057] According to a preferred embodiment, R4, R5, and R6 are each independently selected from H, CH2CH3, CH3, or NH2.

[0058] According to a specific embodiment, the amide material mentioned includes but is not limited to: N-methylformamide, N,N-dimethylacetamide, N,N-dimethylurea, N-methylacetohydrazide, and the like.

[0059] Herein, "alkyl" includes 1-8 carbon atoms saturated straight or branched monovalent alkyl groups, wherein the alkyl group can be independently optionally substituted by one or more substituents described in the present invention. According to some embodiments, the alkyl group contains 1-6 carbon atoms, and according to other embodiments, the alkyl group contains 1-4 carbon atoms. Further examples of alkyl groups include, but are not limited to, methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), 2-methylpropyl or isobutyl (-CH2CH(CH3)2), 1-methylpropyl or sec-butyl (-CH(CH3)CH2CH3), tert-butyl (-C(CH3)3), etc. The alkyl group can be substituted by the substituents described in the present invention.

[0060] The term "aryl" may be a monocyclic, bicyclic, and tricyclic carbon ring system, wherein at least one ring system is aromatic, wherein each ring system contains 3-7 atoms and has only one point of attachment to the rest of the molecule. The term "aryl" may be used interchangeably with the term "aromatic ring", such as aromatic rings may include phenyl, naphthyl and anthracene. Depending on the structure, an aryl group may be a monovalent group or a divalent group, i.e., an arylene group. An aryl group may be substituted with the substituents described herein.

[0061] The term "heteroaryl" refers to a monocyclic ring system in which one or more atoms of the heteroaryl ring are independently optionally substituted by heteroatoms (heteroatoms selected from N, O, P, S, where S or P is independently optionally substituted by one or more oxygen atoms to give groups such as SO, SO2, PO, PO2). The heteroaryl system can be attached to the main structure at any heteroatom or carbon atom to form a stable compound.

[0062] The present invention also provides a perovskite solar cell, comprising:

[0063] Conductive substrate;

[0064] A dense layer, the dense layer is disposed on the conductive substrate;

[0065] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;

[0066] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;

[0067] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;

[0068] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the product of the reaction of the mentioned additive and amide material is added to the perovskite precursor for preparing the perovskite active layer.

[0069] Among them, the conductive substrate can choose a variety of materials, such as FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, PEN / ITO conductive glass. For example, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) glass can be used as the substrate of the battery to provide good optical transparency and conductivity. The dense layer is located on the conductive substrate layer, and the commonly used dense layer materials include but are not limited to TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. Commonly used mesoporous electron transport layer materials include TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. These materials are used to efficiently transfer electrons to the electrode and prevent holes from being transmitted to the cathode. The materials that can be used as mesoporous spacer layers are usually some inorganic oxide materials (such as TiO2, ZrO2, Al2O3). These materials play a role of isolation and protection in perovskite solar cells, and also help to improve the performance of the battery. For example, SiO2 and ZrO2 are often used as spacer layer materials. The spacer layer film prepared by SiO2@ZrO2 nanoparticles has the characteristics of ultra-flatness and crack-free, which can effectively improve the power conversion efficiency of perovskite solar cells. In addition, Al2O3 is also widely used in spacer layer materials, especially when used in combination with ZrO2, which can significantly improve the photoelectric conversion efficiency. According to a specific embodiment, the mesoporous spacer layer material includes but is not limited to ZrO2, SiO2, Al2O3, BaTiO3. The material of the porous counter electrode layer is a carbon material.

[0070] The perovskite active layer is filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer. The perovskite active layer includes a perovskite material, the additives mentioned and an amide material. The perovskite material mentioned is usually composed of an organic-inorganic hybrid perovskite material with an ABX3 structure, such as methylamine lead iodine (CH3NH3PbI3), methylamine lead bromide (MAPbBr3), formamidine lead iodine (FAPbI3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and mixed cations, anions and perovskite materials thereof, etc. The perovskite material, additives and amide materials can be added dropwise to the mesoporous structure, left to stand for a period of time, and annealed on a hot stage at 50-80°C for 1-10 hours.

[0071] The perovskite solar cell mentioned above can be obtained by a common preparation method in the art. According to a specific embodiment, the additive and amide material for the perovskite solar cell are added to the perovskite precursor solution and are jointly filled into the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.

[0072] The technical solution of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. The substances listed in the table of the present invention are used as additives to prepare perovskite solar cells, and they have been verified to significantly improve the photoelectric conversion efficiency of perovskite solar cells. Unless otherwise specified, the reagents used in the embodiments can be obtained commercially, or can be prepared in combination with the common knowledge of those skilled in the art.

[0073] Example 1

[0074] Example 1 uses chloroformamidine hydrochloride (abbreviated as ClFA) to react synergistically with N-methylformamide and N,N-dimethylformamide to improve the performance of the prepared perovskite solar cell.

[0075]

[0076] The battery device preparation method comprises the following steps.

[0077] (1) Glass substrate processing: mainly includes three steps: cutting / laser etching and cleaning.

[0078] Cutting: Use a glass cutter to cut the original glass into the required size. Before cutting, make sure the glass surface is clean to avoid defects during the cutting process. After cutting, grind the glass to smooth the sharp edges.

[0079] Laser etching: Use laser etching equipment to adjust the laser power and parameters to control the etching depth and accuracy, and perform high-precision processing on the glass substrate. Laser etching can remove part of the material to form the desired pattern or structure.

[0080] Cleaning: After cutting and laser etching, the glass substrate is cleaned in an ultrasonic cleaner using deionized water and detergent for multiple rounds to remove residual impurities and contaminants. After cleaning, it is spun or dried to ensure that there is no residual moisture on the surface.

[0081] (2) Preparation of dense layer and printing and sintering of three-layer membrane.

[0082] The diisopropyl di(acetylacetonate) titanate solution is atomized and then sprayed on the FTO surface of the above-mentioned glass, and decomposed at high temperature to obtain a dense TiO2 dense layer, which is then cooled naturally; then a titanium dioxide electron transport layer, a zirconium dioxide spacer layer, and a carbon counter electrode layer are deposited on the glass sprayed with the dense layer by printing layer by layer, and sintered at different temperatures.

[0083] Specifically, a nano-titanium dioxide electron transport layer is deposited on the dense TiO2 layer using screen printing technology, and the pore-forming agent is removed to form a mesoporous titanium dioxide film.

[0084] A zirconium dioxide layer is formed on the mesoporous titanium dioxide film by using a screen printing technique, and then dried at 70° C. to remove the solvent, thereby forming a zirconium dioxide film.

[0085] Finally, a carbon counter electrode layer is deposited on the zirconium dioxide film, usually by screen printing or doctor blade technology, and sintered at an appropriate temperature to ensure its stability.

[0086] (3) Prepare perovskite solution.

[0087] The experiment was divided into a control group and an experimental group.

[0088] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodoformamidine were weighed and dissolved in 800 μL N,N-dimethylformamide (DMF) and 200 μL dimethyl sulfoxide (DMSO) to obtain the control group perovskite precursor solution.

[0089] Experimental group: 1mmol lead iodide, 0.15mmol chloromethylamine, 0.1mmol iodomethylamine, and 0.9mmol iodoformamide were weighed and dissolved in 600μL N,N-dimethylformamide (DMF), 200μL of a mixed solution formed by the reaction of ClFA and N-methylformamide (NMF), and 200uL of dimethyl sulfoxide (DMSO) to obtain the experimental group perovskite precursor solution, wherein the molar ratio of the amount of ClFA additive to the perovskite component was 0.15:1.

[0090] The precursor solutions of the control group and the experimental group were stirred at 50°C for 2 h and then kept for later use.

[0091] (4) Filling of perovskite solution and crystal growth.

[0092] First, cover the non-filled area with tape, and then use a dispenser to drop the prepared perovskite solution on the surface of the carbon film (filling amount is 200-350 mg). After standing for a certain period of time, place the battery in a quasi-sealed device and anneal it on a hot plate at 80°C for 3 hours. After the solvent is completely removed, the battery preparation process is completed, and the control group battery and the experimental group battery are obtained respectively.

[0093] The actual picture of the control group battery prepared is as follows Figure 1 The actual picture of the experimental group battery is shown in Figure 2 Comparing the actual pictures of the experimental group and the comparison group, it can be seen that the perovskite crystallization of the experimental group battery has been greatly improved.

[0094] In addition, the prepared experimental group batteries and control group batteries were tested for photoelectric conversion efficiency (PCE) performance.

[0095] The PCE test of solar cells is carried out by combining a solar simulator and a digital source meter efficiency test system to obtain the JV curve of the test device. Before the test, a standard silicon cell must be used as a reference and the calibrated light intensity must be 1 standard sunlight (AM1.5 G, 100mW / cm 2 ). The scanning range is 16V~-1V, and the scanning step is 0.2V. PCE (photovoltaic conversion efficiency) refers to the efficiency of solar cells in converting received light energy into electrical energy, and is a key indicator for measuring battery performance. PCE is composed of V OC , J SC and FF jointly determine. OC (Open circuit voltage) refers to the voltage difference between the two ends of a solar cell when the external circuit is disconnected. SC (Short-circuit current density) refers to the current density under short-circuit conditions. FF (fill factor) refers to the maximum power point voltage (V MP ) and maximum power point current (J MP ) multiplied by the open circuit voltage (V OC )Short circuit current density (J SC ) product of .

[0096] The performance characterization results of the experimental group and the control group batteries are shown in Table 1 below:

[0097] Table 1 Battery performance characterization results

[0098]

[0099] It can be seen from the results given in Table 1 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0100] Example 2

[0101] Example 2 A perovskite solar cell was prepared by referring to the method of Example 1. Example 2 The performance of the perovskite solar cell was improved by the synergistic reaction of chloroformamidine hydrochloride and N-methylformamide.

[0102] The perovskite precursor solutions of the control group and the experimental group set in Example 2 are as follows:

[0103] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodomethylamine were weighed and dissolved in 800 μL N-methylformamide (NMF) and 200 μL dimethyl sulfoxide (DMSO). The obtained solution is the perovskite precursor solution of the control group.

[0104] Experimental group: 1mmol lead iodide, 0.15mmol chloromethylamine, 0.1mmol iodomethylamine, and 0.9mmol iodomethylamine were weighed and dissolved in 800μL of a mixed solution formed by the reaction of ClFA and N-methylformamide (NMF) and 200μL of dimethyl sulfoxide (DMSO). The result was the perovskite precursor solution of the experimental group, in which the molar ratio of the amount of ClFA additive to the perovskite component was 0.15:1.

[0105] The performance characterization results of the perovskite solar cells prepared in the experimental group and the control group are shown in Table 2 below:

[0106] Table 2 Performance characterization results

[0107]

[0108] It can be seen from the results given in Table 2 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0109] Example 3

[0110] Example 3 A perovskite solar cell was prepared by referring to the method of Example 1. Example 3 The performance of the perovskite solar cell was improved by the synergistic reaction of chloroformamidine hydrochloride and N,N-dimethylacetamide.

[0111] Example 3 The components of the perovskite solution precursor solution of the experimental group and the control group are as follows:

[0112] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodomethylamine were weighed and dissolved in 800 μL N,N-dimethylformamide and 200 μL dimethyl sulfoxide (DMSO). The obtained solution is the perovskite precursor solution of the control group.

[0113] Experimental group: ClFA and N,N-dimethylacetamide were first reacted in a molar ratio of 1:1, and then the mixed solution after the reaction was added to the above control group solution to obtain the experimental group perovskite precursor solution, wherein the molar ratio of the amount of ClFA additive to the perovskite component was 0.15:1.

[0114] The performance characterization results of the perovskite solar cells prepared by the experimental group and the control group are shown in Table 3 below:

[0115] Table 3 Battery performance characterization results

[0116]

[0117] It can be seen from the results given in Table 3 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0118] Example 4

[0119] Example 4 A perovskite solar cell was prepared by referring to the method of Example 1. Example 4 The performance of the device was improved by the synergistic reaction of chloroformamidine hydrochloride and N,N-dimethylurea.

[0120] The components of the perovskite precursor solutions of the control group and the experimental group of Example 4 are as follows:

[0121] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodomethylamine were weighed and dissolved in 800 μL N,N-dimethylformamide and 200 μL dimethyl sulfoxide (DMSO). The obtained solution is the perovskite precursor solution of the control group.

[0122] Experimental group: ClFA and N,N-dimethylurea were first reacted at a molar ratio of 1:0.5, and then the mixed solution after the reaction was added to the above control group solution to obtain the experimental group perovskite precursor solution, wherein the molar ratio of the amount of ClFA additive to the perovskite component was 0.15:1.

[0123] The performance characterization results of the perovskite solar cells prepared by the experimental group and the control group are shown in Table 4 below:

[0124] Table 4 Performance evaluation results of different batteries

[0125]

[0126] It can be seen from the results given in Table 4 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0127] Example 5

[0128] Example 5 A perovskite solar cell was prepared by referring to the method of Example 1. Example 5 The performance of the device was improved by the synergistic reaction of chloroformamidine hydrochloride and N-methylacetohydrazide.

[0129] Example 5 The perovskite precursor solutions of the control group and the experimental group are as follows:

[0130] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodomethylamine were weighed and dissolved in 800 μL N,N-dimethylformamide and 200 μL dimethyl sulfoxide (DMSO). The obtained solution is the perovskite precursor solution of the control group.

[0131] Experimental group: ClFA and N-dimethylacetohydrazide were reacted at a molar ratio of 2:1, and then the mixed solution after the reaction was added to the above control group solution to obtain the experimental group perovskite precursor solution, wherein the molar ratio of the amount of ClFA additive to the perovskite component was 0.15:1.

[0132] The performance characterization results of the perovskite solar cells prepared by the experimental group and the control group are shown in Table 5 below:

[0133] Table 5 Performance characterization results of different batteries

[0134]

[0135] It can be seen from the results given in Table 5 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0136] Example 6

[0137] Example 6 A perovskite solar cell was prepared by referring to the method of Example 1. Example 6 used the following additive (C2H6Cl2N2) to react synergistically with N-methylformamide to improve device performance.

[0138]

[0139] Example 6 The perovskite precursor solutions of the experimental group and the control group are as follows:

[0140] Control group: 1 mmol lead iodide, 0.15 mmol chloromethylamine, 0.1 mmol iodomethylamine, and 0.9 mmol iodomethylamine were weighed and dissolved in 800 μL N-methylformamide (NMF) and 200 μL dimethyl sulfoxide (DMSO). The obtained solution was the perovskite precursor solution of the control group.

[0141] Experimental group: 1mmol lead iodide, 0.15mmol chloromethylamine, 0.1mmol iodomethylamine, and 0.9mmol iodomethylamine were weighed and dissolved in 800μL of a mixed solution formed by the reaction of C2H6Cl2N2 and N-methylformamide (NMF) and 200μL of dimethyl sulfoxide (DMSO). The result was the perovskite precursor solution of the experimental group, in which the molar ratio of the ClFA additive to the perovskite component was 0.15:1.

[0142] The performance characterization results of the perovskite solar cells prepared in the experimental group and the control group are shown in Table 6 below:

[0143] Table 6 Battery performance characterization results

[0144]

[0145] It can be seen from the results given in Table 6 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.

[0146] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementation methods", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0147] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An additive for perovskite solar cells, characterized in that: Having the structure shown in formula (I); Wherein, R1, R2, and R3 are each independently selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino, and substituted or unsubstituted guanidino; X - Selected from halogen anions, SCN - , CN - 、OCN - OH - 、COO - 、CH3SO3 - , or CF3SO3 - .

2. The additive for perovskite solar cells according to claim 1, characterized in that: The R1, R2, and R3 are each independently selected from H, substituted or unsubstituted C 1~4 alkyl, substituted or unsubstituted amino, substituted or unsubstituted amidino, substituted or unsubstituted guanidino, the C 1-4 The alkyl group, amino group, amidino group and guanidino group may be independently substituted by one or more alkyl groups, aryl groups, halogenated alkyl groups, halogenated aryl groups and amino groups.

3. The additive for perovskite solar cells according to claim 1, characterized in that: R1 and R2 are H, and R3 is H, CH2, CH2CH3, or CH2CH2CH2CH3; The X - F - , Cl - OH - .

4. The additive for perovskite solar cells according to claim 1, characterized in that: Select at least one of the following:

5. A precursor solution for perovskite solar cells, characterized in that: Comprising a perovskite material, an additive for a perovskite solar cell according to any one of claims 1 to 4, and an amide material; Optionally, the molar ratio of the additive for perovskite solar cells to the amide material is 0.1:(2-100).

6. The precursor solution according to claim 5, characterized in that The amide material has a structure shown in the following formula (II): wherein R4, R5, and R6 are each independently selected from substituted or unsubstituted phenyl, H, CH3, CH2CH3, CH2CH2CH3, NH2, CH2NH2, CH2CH2NH2, or NHNH2; Optionally, R4, R5, and R6 are each independently selected from H, CH2CH3, CH3, or NH2.

7. A perovskite solar cell, characterized in that: Comprising a perovskite active layer, the perovskite active layer comprising a perovskite material, an additive for a perovskite solar cell according to any one of claims 1 to 4, and an amide material; Optionally, the molar ratio of the additive for perovskite solar cells to the perovskite material is (0.005-0.2):

1.

8. A perovskite solar cell, characterized in that: include: Conductive substrate; A dense layer, the dense layer is disposed on the conductive substrate; A mesoporous electron transport layer, wherein the mesoporous electron transport layer is disposed on the dense layer; A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer; A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer; and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the perovskite precursor for preparing the perovskite active layer is added with the product of the reaction of the additive for perovskite solar cells according to any one of claims 1 to 4 and an amide material.

9. The perovskite solar cell according to claim 8, characterized in that: The conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass; The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3; The material of the porous counter electrode layer is carbon.

10. The perovskite solar cell according to claim 9, characterized in that: include: The additive for perovskite solar cells and the amide material are added to a perovskite precursor solution and are jointly filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.